The Conflict Management Styles and Organizational Behavior of Public School Heads in The New Normal - Mark Stephen Tagarda (Research Synergy Foundation, 2024)
This study evaluated the organizational behavior and conflict resolution approaches used by public school heads in Calamba City's Cluster 9 Division. The study was conducted from April to May of 2023. Survey questionnaires were used in the study's descriptive correlational design and stratified random sampling to determine organizational behavior and conflict management approaches. The participants in the study were the school heads and teaching personnel in Cluster 9. There were 140 target respondents in all, and the cluster consisted of 6 public elementary and 2 secondary institutions. The researcher-made questionnaire underwent reliability testing using Cronbach's Alpha and pilot testing before data collection, with five experts validating it. The four-point Likert scale, mean, and Pearson r were used to assess the degree of organizational behavior and conflict management styles' application. An expert statistician who used thew the SPSS software received the collected data. The findings showed that school heads are proactive and skilled communicators with their staff. They use cooperative and accommodating resolution strategies, which is consistent with a supportive and less autocratic workplace. To improve the practices and utilization of conflict management techniques, a proposed enhancement program named Project CARP (Conflict Activity Resolution Program for School Heads in Cluster 9 Division of Calamba) was developed.